Accountability, Supervision, and Transparency as Determinants of Public Service Performance: Empirical Evidence from a Frontline Local Government Institution - Arfiko, Arfiko Diansyah; Sari, Fifian Permata (Economics and Digital Business Review, 2026)
Introduction/Main Objectives: Public service delivery constitutes a central foundation of governmental legitimacy, particularly in decentralized governance systems where citizen experience shapes institutional trust. This study aims to examine the influence of accountability, supervision, and transparency on citizen-perceived public service performance at the urban village (kelurahan) level. Background Problems: Existing governance scholarship predominantly emphasizes macro-level financial performance and examines governance mechanisms independently. Limited empirical attention has been directed toward frontline administrative units and citizen-centered service outcomes such as responsiveness, accessibility, and satisfaction. Novelty: This study develops and tests an integrative governance–performance model that conceptualizes accountability, supervision, and transparency as functionally interdependent determinants of citizen-perceived service outcomes at the grassroots administrative level. Research Methods: A quantitative descriptive–causal design was employed using census data from 57 service providers at Batu Kuning Urban Village, Indonesia. Data were collected through structured questionnaires and analyzed using multiple linear regression with classical assumption testing. Finding/Results: All governance variables positively and significantly influence public service performance both partially and simultaneously (p < 0.05). Supervision emerged as the most dominant predictor. The model explains 41.9% of the variance in service performance (R² = 0.419). Conclusion: Integrated governance mechanisms significantly enhance citizen-perceived service performance, confirming that coherent accountability, supervisory, and transparency arrangements are critical in frontline administrative settings.